The outcome of antibiotics as surgical prophylaxis in gynecological procedures - a retrospective study in a south Indian hospital - Rozati, Roya; Tahniyath, Fatima; Sharma, R. S.; Mehdi, A. G.; Aiman, A. V.; Dhaded, Sujata R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of the study was to evaluate the outcome of antibiotics as surgical prophylactic measure for gynecological procedures in a south Indian Hospital. Methods: A retrospective study was conducted in 150 women who underwent caesarean, hysterectomies, Dilation and Curettage, myomectomy, operative vaginal delivery and were prescribed antibiotics. The data regarding demographic details, presenting complaints, parity, obstetrics history, diagnosis and need for surgery was evaluated. Results: A total of 206 women admitted with surgical procedures performed were taken into consideration of which 150 were prescribed antibiotics alone but 26 patients did not respond to treatment and were given other antibiotics, 30 patients were shifted to other specialist departments or other hospital for better treatment due to economic status, hence 150 patients formed the study population. The mean age was years. Patients above years were mostly seen. Conclusions: In our study, cefuroxime appeared to be effective in prophylaxis against infections. Metronidazole appeared to be ineffective compared to Cefuroxime. Combination of Cefuroxime and metronidazole was less effective compared to Amoxicillin and potassium clavunate. Cefazolin was commonly prescribed for gynecological procedures.